Formation of Fe-C-Si ternary composite coating on CP-titanium and its tribological interaction with Jatropha oil - Maleque, Md. Abdul; ., W. Saffin; Ahmed, A. S (2016)
The main aim of this study is to develop ternary composite coating through incorporation of Fe-C-Si ternary powder mixtures on CP-Ti substrate and characterize the microstructure, hardness and wear behavior of composite coated CP-Ti in presence of Jatropha oil. In this work, the surface of commercial purity titanium (CP-Ti) was modified using a tungsten inert gas (TIG) surface melting technique. The wear behavior of coated CP-titanium was performed using pin-on-disk machine at room temperature under Jatropha-biodiesel lubricated condition. The melt track has dendritic microstructure and the dendrites were identified as TiC and Fe3C precipitates which were homogenously distributed throughout the melt pool. This Fe-C-Si ternary composite coating enhanced the surface hardness of CP-Ti significantly from 175 HV for the untreated substrate to ~800 HV for the Fe-C-Si coated CP-Ti due to the formation of intermetallic compounds of TiC and Fe3C. The wear results showed that less wear volume loss was observed on the composite coated CP-Ti in presence of Jatropha-biodiesel compared to uncoated CP-Ti. The achievement of this hard Fe-C-Si composite coating on the surface of CP-Ti can broadened new prospect for manufacturing more effective and durable components or structure which can be used for many engineering applications that use biodiesel under different tribological variables.